2021
DOI: 10.1038/s41598-021-82597-3
|View full text |Cite
|
Sign up to set email alerts
|

A self-referenced in-situ arrival time monitor for X-ray free-electron lasers

Abstract: We present a novel, highly versatile, and self-referenced arrival time monitor for measuring the femtosecond time delay between a hard X-ray pulse from a free-electron laser and an optical laser pulse, measured directly on the same sample used for pump-probe experiments. Two chirped and picosecond long optical supercontinuum pulses traverse the sample with a mutually fixed time delay of 970 fs, while a femtosecond X-ray pulse arrives at an instant in between both pulses. Behind the sample the supercontinuum pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…We have demonstrated that the Maxwell-Garnett theory of dielectric mixtures, where we assume a dielectric mixture of a diamond host material and electronic polarons, describe the observed measurement very well. With the high versatility of this self-referenced timing tool, even in-situ arrival time measurements in a unstable free-flowing liquid jet are possible 37 . This can also be used to quantify the robustness of the Maxwell-Garnett model for various materials and liquids in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that the Maxwell-Garnett theory of dielectric mixtures, where we assume a dielectric mixture of a diamond host material and electronic polarons, describe the observed measurement very well. With the high versatility of this self-referenced timing tool, even in-situ arrival time measurements in a unstable free-flowing liquid jet are possible 37 . This can also be used to quantify the robustness of the Maxwell-Garnett model for various materials and liquids in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that the Maxwell-Garnett theory of dielectric mixtures, where we assume a dielectric mixture of a diamond host material and electronic polarons, describe the observed measurement very well. With the high versatility of this self-referenced timing-tool, even in-situ arrival-time measurements in a unstable free-flowing liquid jet are possible 33 . This can also be used to quantify the robustness of the Maxwell-Garnett model for various materials and liquids in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…There are two main reasons for a change in the kick from shot to shot. The first is the relative timing jitter between the X-ray and the streaking pulse 24 26 , which is unavoidable due to the stochastic generation process of the SASE mechanism and additional fluctuations in arrival time caused by air fluctuations, thermal expansion in optomechanical components, and general synchronization errors between the two separate laser pulses. The second reason for variations of the kick is the random change of the carrier–envelope phase of the streaking laser from shot to shot.…”
Section: Application Case: Angular Streakingmentioning
confidence: 99%